PERANAN DESA ADAT (PAKRAMAN) DAN SEKAA TARUNA DALAM MENUNJANG PARIWISATA DI BALI - A.A.Ayu Ngr. Harmini; Solihin Solihin (Politeknik Negeri Bali, 2013)
Tourism is like a fire, it can cook your food, but it can also burn your house Down”. Tourism effects to both negative and positive of human life especially to the local people where the tourism being developed. To minimize the negative impact and to maximize the positive one is required the involvement of Balinese traditional Village (desa pakraman) in tourism development, and tourism is expected to support the conservation of the nature environment, people and local culture and protect the negative impact to the young Balinese traditional people (Sekaa Teruna). Simple tourism is a best choice for the young generation because it can create or prevent the local knowledge/local genius. Unrealized there are two kinds of culture are owned by local people of Bali such foreign culture/tourism(touristic) culture and local culture cultural tourism. The Global Tourism/touristic culture must be implemented to create the convert of foreign tourist during their visit and the local culture must be conserved to attract and tide them in order to see, admire and enjoy it. Base on the above explanation as a religious social institution and as place of born, life, growth and developed of tourism, Balinese Traditional Village has the important role as a filter in protecting the tourism bad impact imported by foreign tourist. To protect and grow the simple tourism,